FROM THE HISTORY OF ECONOMIC RELATIONS OF THE CENTRAL ASIAN KHANATES WITH THE OTTOMAN STATE - Rahmonqulova Z. B. (TARIXIY TADQIQOTLAR, 2025)
The article examines the economic relations of the Central Asian khanates with the Ottoman Empire, and relies on a number of sources and studies within the framework of the topic. It also provides information about the cities and goods that were of great importance in trade relations between the countries.